THE THEORETICAL RELEVANCE AND EFFECT OF USING JIGSAW STUDENTS VOCABULARY MASTERY - Marciana Ana; Rissa San Rizqiya; Hendra Husnussalam (PROJECT (Professional Journal of English Education), 2024)
This literature review aims to analyze jigsaw technique in teaching vocabulary effect. Vocabulary is the first important in language learning component, to mastering four language skill. In this study, researchers are figure out on jigsaw effectiveness whether the results are positive or negative, and are also looking for the differences and similarities of the journal entries. The associated journal paper was identified and chosen using Google scholar and the educational research center. In the seven journals, there were five to use the same design research is quantitative research and one jurnal using qualitative research an tthe other one library research. Many similarities from the seven journals, in obtaining data quantitative using quasi experimental and pre experimental and the data using tukey tests, anova and purposive. To qualitative the researchers employed observation, questionnaire, interview, and document analysis. And for library research,  just trying to figure out how to teach grammar in English using jigsaw techniques and the benefits of doing so.Although the settings are different whether it's the media but all the positive results are jigsaw technique can improve students’ vocabulary ability, can enhance student interaction, also jigsaw technique can improve students' vocabulary ability, as well as their interaction with the teacher and other students. It was also effective in English vocabulary development.